Market Structure, Conduct and Performance of Scad (Decapterus russeli) in Kota Ambon - Yolanda MTN Apituley; Yoisye Lopulalan; Revalda Amanda Salakory; Dionisius Bawole (Jurnal Manajemen & Agribisnis, 2018)
This research is aimed to analyze the marketing system of Scad (Decapterus russeli) by analyzing the market structure, behavior, and performance. It was conducted in traditional markets: Mardika and Transit Passo, Ambon from September to December 2014. The method used was survey for 40 of 45 fish traders in these markets, selected in simple random sampling. The analyses used included: 1). Integration of vertical market, 2). Elasticity of price transmission, and 3). Pricing efficiency. The results show: (1) market structure of scad in Ambon is not integrated and leads to oligopoly; (2) change of 1% at the consumers’ price level leads to less than 1 % of price change in the fishermen’s price level, indicating that scad marketing system is inefficient; and (3) the marketing system of scad in channel 3 is inefficient. The smallest share (89%) was also showed in this channel. Scad market structure was not perfectly integrated for the oligopoly practice by traders. Therefore, dependence of fishermen on traders should be reduced i.e. by giving assistance such as loans with low interest rates especially in no fish season. Communication network should also be expanded so that market information can be transmitted perfectly to all marketing agencies in Ambon. The government should control the price fluctuations by setting the minimum price (floor price) and maximum price (ceiling price) in order to create price stability.Keywords: conduct market, oligopoly market, performance market, scad structure, fish traders